Epidemiological and clinical profile of paediatric snake bite patients at a tertiary care centre of Himachal Pradesh, India - Sood, Arvind; Rana, Aman; Kumar, Pancham (International Journal of Contemporary Pediatrics, 2020)
Background: Pediatric snake bite cases are frequently encountered at health care centers of Himachal Pradesh. It is a medical emergency which require early hospitalisation and immediate medical intervention. This study determines the epidemiological and envenomation details along with clinical profile and management of pediatric snake bite patients in Himachal Pradesh, India. Methods: This prospective clinico-epidemiologic study included 30 paediatric snake bite cases reported at Department of Paediatrics, IGMC, Shimla. Demography, envenomation details, first aid and treatment, antivenom administration and outcome were recorded for all patients. Results: Of the total 30 cases, 56.6% were males and 43.3% were females. All patients were resident of rural areas and most of them belonged to middle socioeconomic status. Most (56.7%) snake bites occurred between 6pm to 12am and peak time was during rainy season. More cases of hemotoxic envenomation were observed as compared to neuroparalytic envenomation. Most common hematologic abnormalities were hematuria (4.8%) and epistaxis (4.8%). Respiratory paralysis, ptosis and opthalmoplegia were the most common presentation in patients with neuroparalytic envenomation. Clinical profile of patients showed thrombocytopenia (26.7%), prolonged PT/INR (76.6%) and 36.7% had prolonged activated partial thromboplastin time. All symptomatic patients were given ASV as primary treatment out of which 79.2% patients required more than 10 vials of ASV. Most common complication observed in neuroparalytic envenomation was respiratory failure (33.3%) and in hemotoxic envenomation was coagulation failure (66.7%). Only 3.3% case fatality was observed in this study. Conclusions: Snake bite in children is a medical emergency in hilly state of Himachal Pradesh where people still follow traditional first aid methods and treatment protocol. A widespread awareness programme is needed to propagate the newly advised first aid methods to prevent mortality by early hospitalization and administration of ASV.